ANALISIS FAKTOR YANG MEMENGARUHI PERILAKU PEDAGANG ETNIK TIONGHOA DALAM MEMANFAATKAN JASA BANK SYARIAH - Gafur, Abdul (At-Taradhi, 2014)
The existence of a number of ethnic Chinesetraders who usingthe services of sharia bank constitute the interested phenomenon to be studied and analyzed using factor analysis techniques. As a result, factor of religion, attitude, and social status are the most dominant factor that influence their behavior towards Islamic banks.